(untitled) (Public Sector Economics - submission site, 2020)
This paper surveys the literature on immovable property taxation along two dimensions prevalent in the literature: i) according to the type of real estate over its life-cycle and ii) according to the type of tax. The first strand of the literature agrees that immovable property taxation should be neutral to avoid distortionary behaviour vis-a-vis other assets/consumption goods. However, the neutrality benchmark and hence taxation to be chosen depend on the theoretical view taken. The second strand assesses one type of property tax at a single point in time with respect to the considerations of efficiency, equity, fiscal federalism and political economy. Most of this strand of the literature focuses on recurrent property taxation on residential property, which has a lot of theoretical merits. A key message of both strands is that reaping theoretical merits of immovable property taxation in practice is hindered by tax design issues and political economy issues.